Thesaurus on Philippine environment - Sebastian, Romeo A.; Wood, Ma Rosario G.; Serrana, Milagros S. (Makati City, 2005)
This book filipinos in learning more about the state of the Philippine environment. Aimed with more accurate facts, they will be aware of the need to protect their land, their rich socio-cultural-spiritual heritage, and their patrimony. This thesaurus will guide them through their quest in gathering more information towards environmental protection and management. The compilation of a thesaurus on the Philippine environment is a first to be undertaken in the field of environment in this country. There are existing reference materials but not in a thesauri approach.
Keywords: Nature and nurture Philippines- Dictionaries